Effects of COVID-19 on Sudanese Enterprises - World Bank (World Bank, Washington, DC, 2021)
As with other countries, Sudan has been hit hard by the Coronavirus (COVID-19) pandemic. The Sudanese authorities attempted to act quickly in the face of the spreading virus. The Government has established a high-level emergency committee to oversee the operations to deal with the Coronavirus (COVID-19) pandemic. In addition to Coronavirus (COVID-19) impacts, major constraints are affecting the performance and employment levels of business enterprises, particularly private MSMEs. The objective of the Sudan High Frequency Survey on Coronavirus (COVID-19) is to quickly collect enterprise-level information, using phones, to monitor the crisis and assess the dynamics of the impacts of Coronavirus (COVID-19) on MSMEs in Sudan. The survey is expected to help inform dialogue and mitigation measures. The survey is implemented jointly by the Central Bureau of Statistics (CBS) and the World Bank. The key findings of the survey are summarized in terms of enterprise closings, impact on sales and employment, channels affecting operations, adjustment mechanisms, enterprise perceptions, and government policies.